Impacto de inseticidas aplicados em soja sobre abelhas melíferas - Jung, Affonso Hermeto (2014)
This study aimed to investigate the time foraging and spatial-temporal distribution of Apis mellifera as well as its influence on crop productivity, in addition to analyzing the botanical origin and insecticide residues in honey throughout the flowering period. The study was conducted on soybean crop in 2012/13, in two areas in Hulha Negra - RS. In the first area, referring to commercial farming of 19.70 acres, four model Langstrogh hives were placed at the ends and divided into 4 areas/treatments performed in bands, the following insecticides: 1- Lambda-cyhalothrin+ thiamethoxam; 2- Imidacloprid+Beta-cyfluthrin, 3- Acephate and 4 - Untreated. While in the second location, each treatment was installed in a cage of 32 m2, four hives/core, one per cage. The installation of colonies in both study areas, occurred on the pre-flowering and spray treatments 15 days after. In the study of foraging were observed and sampled the number of bees in the flowers, in certain places, for 5 minutes every hour, between 7 and 19 hours. To research the distribution of pollinators was marked the perimeter of the area with the aid of a GPS navigation, with dimensions of 50 x 50 grid of me 79 sample points, with population density estimated by visual observations. The yield factors were assessed weight of 100 grains (g) and production (g/3m2), which was converted to kg/ha-1. The honey gathering was held at the end of flowering and multiresidue samples were sent to the Laboratório de Análise de Resíduos de Pesticidas (LARP). As for the detection of biological origin in the honey samples were sent to the Laboratory of Apiculture, UFRGS. The foraging bees foraged in soybean flowers in search of nectar and pollen, preferably in the period from 10 to 13 hours. The maps show the total density of the random distribution of bees due to the wide availability of resources. The soybean bloom occurred predominantly foraging by foraging bees. Treatment with insecticide Acephate contaminated honey produced, and treatments of closed cages with bees no effect on crop productivity.